Especiação de mercúrio em cogumelos por LC-CVG-ICP-MS: avaliação de procedimentos de extração - Pilz, Camila (2009)
In this work, different sample preparation procedures for determining inorganic (in Hg2+ form) and organic mercury (in methylmercury form CH3Hg+) in edible mushrooms were evaluated. Conventional, microwave (MW) and ultrasound (US) assisted extractions combined with water, hydrochloric acid and L-cysteine solutions were tested. Liquid chromatography-chemical vapor generation-inductively coupled plasma mass spectrometry (LC-CVG-ICP-MS) was used for Hg species determination. Total Hg was determined by CVG-ICP-MS after sample decomposition. The influence of the main parameters on Hg species extraction, such as extraction solutions concentration, temperature, US amplitude and extraction time were investigated. Hg species conversion was observed in all conditions when HCl was used as extractor medium. Besides, Hg species extraction from the samples is not quantitative. No Hg species conversion was observed when water and 1.0% (m/v) L-cysteine solution were used. However, the extractions were not quantitative when water was used. Quantitative extractions were obtained only when 1.0% (m/v) L-cysteine was used as extraction solution for conventional and US assisted extractions. The optimized conditions for these procedures (US 20% for 1 min and conventional extraction for 12 h at 25 °C) provided extraction efficiencies higher than 86% for the sum of the Hg species, while only up to 88% of the Hg species were extracted when MW heating was used. The relative standard deviation (RSD) is lower than 8.0 and 13% for Hg2+ and CH3Hg+, respectively. Detection limits for US, MW and conventional extractions (using L-cysteine) were 0.41 and 0.35 ng g-1, 0.64 and 0.90 ng g-1, and 1.41 and 0.11 ng g-1 for Hg2+ and CH3Hg+, respectively. The procedures were evaluated using analyte recovery tests of Hg species and by analysis of certified reference material (DOLT-3). Recoveries in the range of 89 to 109% for Hg2+ and 96 to 113% for CH3Hg+ were obtained. The agreement of the obtained results for DOLT-3 were in the range of 88 to 93% for CH3Hg+ and 95 to 102% for total Hg, respectively. US assisted extraction was considered simpler and faster than the other procedures, being more suitable for Hg species extraction from edible mushrooms.